2013
DOI: 10.1155/2013/435260
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical and Structural Properties of Blend Lignin-PMMA

Abstract: Thisin vitrostudy investigated the mechanical and structural characteristics of lignin-added PMMA resin composites at concentrations of 1, 3, and 5% by weight. Four sample groups were formed. For the transverse strength test, the specimens were prepared in accordance with ANSI/ADA specification number 12, and for the impact test ASTM D-256 standards were used. With the intent to evaluate the properties of transverse strength, the three-point bending (n=10) test instrument (Lloyd NK5, Lloyd Instruments Ltd., Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…[26][27][28] However, this behavior was shown to vary for certain polymeric systems as shown in a study on PMMA based Lignin blends where, Lignin was shown to reduce transverse modulus & strength but improve impact resistance. [29] The structural complexity of Lignin also provides prospect for chemical modification. It was found that alkylated Lignin blended with PP to increase compatibility, improved both the impact strength and damping effect even with upto 40wt% alkylated Lignin content.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] However, this behavior was shown to vary for certain polymeric systems as shown in a study on PMMA based Lignin blends where, Lignin was shown to reduce transverse modulus & strength but improve impact resistance. [29] The structural complexity of Lignin also provides prospect for chemical modification. It was found that alkylated Lignin blended with PP to increase compatibility, improved both the impact strength and damping effect even with upto 40wt% alkylated Lignin content.…”
Section: Introductionmentioning
confidence: 99%
“…This may due to the lower content of lignin present in the natural fiber which enhances the impact strength of the composites. 39,40 Lignin content of banana fiber is lower than abaca fiber.…”
Section: Comparative Analysismentioning
confidence: 99%
“…In studies where the mixing of different polymers can be achieved, it has been observed that the resulting blend usually has the superior properties of the components. [1][2][3] Polyvinyl chloride (PVC) is a common commercial polymer. Due to its halogen content, it shows superior properties in terms of nonflammability and low-cost features.…”
Section: Introductionmentioning
confidence: 99%
“…In studies where the mixing of different polymers can be achieved, it has been observed that the resulting blend usually has the superior properties of the components 1–3 . Polyvinyl chloride (PVC) is a common commercial polymer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation